Comparative evaluation of storage time on the quality of platelet concentrates prepared from buffy coat at ambient temperature - Taggar, Gurpreet Kaur; Singh, Tarun Jot; Kumar, Rajesh (International Journal of Research in Medical Sciences, 2023)
Background: Buffy coat-platelets concentrates (BC-PC) are prepared within 6-8 hours of blood collection with 1-2 hours of hanging period which imposes time constraints and logistic problems when collecting blood from blood donation camps in wide geographic areas. Methods: In our prospective study of one year at Dayanand Medical College and Hospital, Ludhiana we prepared 50 units of BC-PC after hanging BC for 2 hours and another 50 after storing BC O/N at ambient temperature. Platelet (plt) count, WBC contamination and other biochemical parameters in both groups of PC were analyzed on day 1 and day 5 of preparation. Results: The mean plt counts of O/N BC-PC on day 1 was 8.36±1.22 × 1010, significantly higher than that of F (fresh) BC-PC (7.44±0.81 × 1010). On day 5, F BC-PC showed 6.21±0.88 × 1010 count while it was 6.87±0.96 × 1010 in O/N BC-PC. WBC contamination was lower in O/N BC-PC. On day 1, in F BC-PC WBC contamination was observed as 4.44±2.02 × 107 while in O/N BC-PC it was 3.19±3.33 × 107. On day 5, in F BC-PC WBC contamination was observed as 3.77±0.66 × 107 while in O/N BC-PC it was 2.92±1.71 × 107. Results of biochemical parameters (pH, pO2, pCO2, glucose) were significantly higher and better in F BC-PC but both methods of preparation provided plts optimal survival conditions throughout storage period. Conclusions: O/N BC-PC provides a better-quality product while solving logistic problems.